2019
DOI: 10.2166/washdev.2019.180
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between shared sanitation facilities and diarrhoeal and soil-transmitted helminth infections: an analytical review

Abstract: Shared sanitation is widely proposed as a means to increase access to improved sanitation. There are few reports of a causal relationship between the use of shared sanitation and community-acquired diarrhoea. This paper presents an analytical review of studies that have investigated the relationship between the use of shared sanitation and the prevalence of (1) diarrhoeal disease and (2) soil-transmitted helminth (STH) infections. Data were extracted from the reviewed literature to calculate odds ratios (ORs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 58 publications
1
17
0
1
Order By: Relevance
“…These challenges are similar to those identified by other studies, which emphasised issues such as water unavailability, poor maintenance, toilet misuse or abuse due to poor behaviour, lack of cleaning materials, as well as conflicts or quarrels-physical fights, and exchange of insults, especially among women when users soiled facilities and/or children dirtied toilets [6,49].…”
supporting
confidence: 79%
“…These challenges are similar to those identified by other studies, which emphasised issues such as water unavailability, poor maintenance, toilet misuse or abuse due to poor behaviour, lack of cleaning materials, as well as conflicts or quarrels-physical fights, and exchange of insults, especially among women when users soiled facilities and/or children dirtied toilets [6,49].…”
supporting
confidence: 79%
“…A similar study conducted using data from 51 countries' demographic and health surveys found that shared sanitation appears to be a risk factor for diarrhoea although differences in socioeconomic status are important [27]. An analytical review study conducted by Ramlal et al in 2019 also found that the use of shared sanitation showed a significant increase in diarrhoeal disease, with an overall OR of 2.39 (85% CI 1.15-8.31) [28].…”
Section: Discussionmentioning
confidence: 99%
“…Shared sanitation facilities are associated with an increase in diarrheal diseases, but this association was not statistically significant [ 19 ]. Approximately, 70% of households had a shared facility in Sierra Leone [ 20 ]. Our findings are greater than what was found in a study conducted in India where 25% of the study respondents shared toilets [ 17 ].…”
Section: Discussionmentioning
confidence: 99%